If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -32 = 22x Reorder the terms: -32 + 6x = 22x Solving -32 + 6x = 22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22x' to each side of the equation. -32 + 6x + -22x = 22x + -22x Combine like terms: 6x + -22x = -16x -32 + -16x = 22x + -22x Combine like terms: 22x + -22x = 0 -32 + -16x = 0 Add '32' to each side of the equation. -32 + 32 + -16x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + -16x = 0 + 32 -16x = 0 + 32 Combine like terms: 0 + 32 = 32 -16x = 32 Divide each side by '-16'. x = -2 Simplifying x = -2
| 4x+15=71 | | 36x^2-24x= | | -3x-19=-43 | | 32+x=90 | | x+58=90 | | -5-(15y-1)=2(7y-16)y | | (y+4)=5Y | | 3a-5=2(4a-9) | | 5(x-2)=4(2x+5) | | 3+2(k+1)=3k+6 | | 2a+3x-3a+7xy+6a-2b= | | 4p^2-6p+1=0 | | 30=20+2r | | 9(I+2)=3(I-2) | | 7(g-2)=5(g+4) | | 6n-7=5n+8 | | 102-3x=15x+18 | | 102-3x=15x | | 2x+10=-90-8x | | 13-10x=112-31x | | 111-4x=4x+7 | | 0-6x=7-7x | | 16x-16y= | | 13-10x=112-3x | | 108-5x=9x+24 | | -59-10x=9x+17 | | 2x+7=43-2 | | 3x+6=-104-8x | | 4x-5=14-115 | | -19x-2x=11-7x | | 7a+5b+7c=36 | | 5x+25=14x-47 |